Notary’s Responsibility As Recipients of Imprest Due To Cancellation of Sales And Purchase Binding Agreement Deed - Brenda Kharisman Rahardjo; Sulistyandari Sulistyandari (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The notary has been disputed several times by the parties since he was proven to have violated his position. In one of the cases occurred based on the verdict Number: 1378K/Pdt/2017, the buyer entrusted advance money to the notary, however, there was a cancellation, where the notary did not fully return the advance money. Purpose of this study is to analyse the responsibility of a notary as a recipient of imprest due to the cancellation of the binding sale and purchase of underhand agreement. The research method is normative, using secondary data from literature studies, including primary, secondary, and tertiary legal sources. Notary are based responsible in person and subject to administrative sanctions for violating the code of ethics by the Notary. One of the characteristics of civil law is as a compliment, and the advance money can be returned to the buyer.Keywords: Responsibility, Notary, Advance money, Sales and Purchase Agreement Deed